Effects of health education during public health emergencies on the health literacy, emotion and coping style of Chinese junior middle school students: a randomized controlled trial - Zhou Wang; Tingye Gao; Guangjian Li; Gengjuan Dong; Yan Zhan; Bingqin Wang; Xugui Sun (BMC, 2023)
Abstract Background Schools are high incidence places for public health emergencies. Good health literacy helps students cope with public health emergencies. Overall, the health literacy of young students is relatively low. Health education can promote health literacy, but the health education related to public health emergencies for Chinese junior middle school students needs to be improved. To design and implement health education courses related to public health emergencies for junior middle school students and examine the impact on their health literacy, emotions, and coping styles. Methods From March to December 2022, 724 students in Grade 7 and Grade 8 of two junior middle schools in Changzhou were randomly divided into a course group (n = 359) and a control group (n = 365). The course group received an age-appropriate health education course that addressed public health emergencies; there were 12 classes, one per week. The control group received general health education. One week before and after the courses, the two groups of students were assessed with the Adolescent Health Literacy Evaluation Scale under Public Health Emergencies (AHLES-PHE), the Depression Self-Rating Scale for Children (DSRSC), the Generalized Anxiety Disorder 7-item scale (GAD-7), and the Simplified Coping Style Questionnaire (SCSQ). Results After the courses were completed, the scores of AHLES-PHE [156.0 (45.0,180.0) vs. 165.0 (54.0,180.0), P < 0. 05] in the course group increased significantly. The positive rate of DSRSC [81 (22.6%) vs. 57 (15.9%), P < 0.05] and GAD-7 [45 (12.5%) vs. 29 (8.1), P < 0.05]in the course group were significantly lower than those before courses. There was no significant difference in the above indices before and after courses in the control group (P > 0.05). Conclusion This suggests that the health education courses related to public health emergencies designed in this study has an effect on improving health literacy, depression and anxiety in junior middle school students.